Determination of the prognosis in patients who presenting impacted maxillary canines in the Faculty of Dentistry of the University of Antioquia - Upegui-Zea, Juan Carlos; Echeverri-González, Elizabeth; Ramírez-Ossa, Diana Milena; Restrepo-Narváez, Leidy Marcela (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: maxillary canine impaction is a rare alteration in the eruption pathway that must be diagnosed and prognosticated on time. A descriptive analysis was performed in a sample of 18 patients of the School of Dentistry of the University of Antioquia in Medellín, Colombia, in order to collect epidemiological information and apply some radiographic maxillary canine impaction analysis to verify its predictive association. Methods: a clinical evaluation of the patients with canine maxillary impaction was carried out and a panoramic radiographs and three periapical of each studied tooth were taken, scanned, and digitally traced, then Lindauer, Warford, Power and Short, and Clark analysis were performed. Results and conclusions: a prevalence of canine impaction of 2,9% was found, significantly higher in females, in the first quadrant, in a labial location and with an associated adjacent lateral incisor malposition. Additionally, a high concordance and a positive association between Warford and Power and Short analysis was noted, but not with the Lindauer analysis. It was concluded that to predict the prognosis of canine maxillary impaction it is valid to apply the angular as well as the sector analysis in panoramic radiographs.